IMPLEMENTATION OF SHARIA BANKS - Nofinawati, Nofinawati (AL-QARDH, 2018)
Social function of Sharia Banks is to receive funds i.e. zakat, infaq, sedekah, wakaf, hibah, and distribute them in accordance to sharia laws under the banks